2020
DOI: 10.1007/978-3-030-58558-7_42
|View full text |Cite
|
Sign up to set email alerts
|

SRFlow: Learning the Super-Resolution Space with Normalizing Flow

Abstract: Super-resolution is an ill-posed problem, since it allows for multiple predictions for a given low-resolution image. This fundamental fact is largely ignored by state-of-the-art deep learning based approaches. These methods instead train a deterministic mapping using combinations of reconstruction and adversarial losses. In this work, we therefore propose SRFlow: a normalizing flow based super-resolution method capable of learning the conditional distribution of the output given the lowresolution input. Our mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
279
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 277 publications
(279 citation statements)
references
References 47 publications
0
279
0
Order By: Relevance
“…However, this approach does not allow the analyst to judge the real capacity of the model to create a new image that has not been degraded by bicubic convolution beforehand. Recent research has tried to overcome this difficulty [26,8,27]. However, these new architectures are beyond the scope of our study and should be the subject of further work.…”
Section: Image Resolution Improvement With Esrganmentioning
confidence: 98%
See 3 more Smart Citations
“…However, this approach does not allow the analyst to judge the real capacity of the model to create a new image that has not been degraded by bicubic convolution beforehand. Recent research has tried to overcome this difficulty [26,8,27]. However, these new architectures are beyond the scope of our study and should be the subject of further work.…”
Section: Image Resolution Improvement With Esrganmentioning
confidence: 98%
“…Image resolution enhancement is called super-resolution (SR) and is currently a very active research topic in EO image analysis [4][5][6] and computer vision in general, as shown in [7]. However, SR is inherently an ill-posed problem [8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Addressing the problem has been proven to be useful in many practical cases, such as medical imaging [1], [2], infrared imaging [3]- [5] and remote sensing imaging [6]- [8]. From mathematical point of view, SISR needs to build a degradation model from high-resolution(HR) images to low-resolution(LR) images and fit the inverse function [9]. The goal of SISR is to generate high-quality super-resolution(SR) images with clear details that are as close as possible to HR images.…”
Section: Introductionmentioning
confidence: 99%